2018
DOI: 10.1002/chem.201705307
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Indistinct Fe−N Stretching Bands in Iron(V) Nitrides by Photodissociation Spectroscopy

Abstract: We report for the first time infrared spectra of three non‐heme pseudo‐octahedral iron(V) nitride complexes with assigned Fe−N stretching vibrations. The intensities of the Fe−N bands in two of the complexes are extremely weak. Their detection was enabled by the high resolution and sensitivity of the experiments performed at 3 K for isolated complexes in the gas phase. Multireference CASPT2 calculations revealed that the Fe−N bond in the ground doublet state is influenced by two low‐lying excited doublet state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…17 Complexes 2 and 3 have been characterized by 57 Fe Mössbauer and X-ray absorption spectroscopy coupled with DFT calculations. 13,14,16 It has been concluded that both complexes are best described as genuine low spin iron(V)-nitrido compounds. In addition to these tetragonal species, Smith, Meyer, and co-workers reported synthesis and spectroscopic and structural characterization of a trigonal iron(V)-nitrido compound, [Fe V (N)(PhB( t BuIm) 3 )] + ( 4 , PhB( t BuIm) 3 – = phenyltris(3- tert -butylimidazol-2-ylidene borate).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Complexes 2 and 3 have been characterized by 57 Fe Mössbauer and X-ray absorption spectroscopy coupled with DFT calculations. 13,14,16 It has been concluded that both complexes are best described as genuine low spin iron(V)-nitrido compounds. In addition to these tetragonal species, Smith, Meyer, and co-workers reported synthesis and spectroscopic and structural characterization of a trigonal iron(V)-nitrido compound, [Fe V (N)(PhB( t BuIm) 3 )] + ( 4 , PhB( t BuIm) 3 – = phenyltris(3- tert -butylimidazol-2-ylidene borate).…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, complexes 2 and 3 also undergo facile decay by dimerization of the Fe V =N groups, eventually yielding monomeric ferrous complexes and releasing N 2 . 16,25 Because complexes 1 – 3 cannot persist in fluid solutions, their reactivity studies relied on in situ spectroscopic methods. For instance, complexes [Fe V (N)L] 2+ , 2 and 3 were shown to be capable of activating C—H or C=C bonds of organic substrates on the basis of the mass fragmentation analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculations can also reproduce the Fermi doublet arising from the coupling between the Fe‐ 18 O stretching band and the ligand band at 926 cm −1 . To compensate for the incorrect prediction of the ν(Fe‐O) force constant, we increased the mass of the O atom in 1 1 + to 19.1, which moved the ν(Fe‐O) vibration to the correct position [53] of ≈960 cm −1 (Figure 4 b, second panel, red trace). Then increasing this mass by the 18/16 ratio to a value of 21.5, we can clearly observe the Fermi doublet like in the IRPD experiment (compare Figure 4 a, red trace and Figure 4 b, second panel, red trace).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the peaks at 2929 and 3135 cm –1 could be due to the stretching mode of C–H from the aromatic ring and the aliphatic chain in 2‐MIM, respectively , . According to the literature, the IR peaks of Cu–N, Fe–N and Ni–N stretch at 460, 855 and 525 cm –1 respectively . We tried to use FT‐IR to analyze the coordination modes between metal and unsaturated ligands on ZIF‐67 surface, but there is no obvious difference between metal derivatives and ZIF‐67 because the amount of Fe/Cu/Ni in the sample is too low to be detected.…”
Section: Resultsmentioning
confidence: 99%